PYROLYSIS OF PINE WOOD WITH POTASSIUM CARBONATE AND CALCIUM HIGROXIDE AS A CATALYST - Francio, Matheus; Silva, Michel Brasil (Anuário Pesquisa e Extensão Unoesc Videira, 2017)
The catalytc reaction of pine wood occured in a fixed bed reactor with a mean temperature of 700°C. The catalysts studied were the potassium carbonate and calcium hidroxide. The potassium carbonate showed stronger catalysis for decomposition of cellulose, hemicellulose and lignin. This happened because this catalyst provided two reaction stages with liquid products generating a greater quantity of solid and gaseous products. With the addicion of 17,7% wt of potassium carbonate the catalyst provided low formation of liquid products such as alcohols and aldehyds, as well as formed smaller amounts of gases such as acids, furans and guaiacols. In the other hand increased phenols, alkenes, hidrogen, carbon dioxide and carbon monoxide. In alkaline catalysis with calcium hidroxide, the formation of undesired liquid products in this type of process, was noted. With about 22%wt concentration of the catalyst the best result was obteined with the dissapearance of liquid products like acids and aldehids. The use of this catalyst only increase the production of hidrogen.